Synergistic Enhancement of Lignocellulosic Biomass Saccharification via Ultrasound-Assisted Pretreatment with Magnetic Fe₃O₄ - Hanif Ardhiansyah; Astrilia Damayanti; Zuhriyan Ash Shiddieqy Bahlawan; Serlia Fitri Sadan; Nurul Khusna; Karenina Hakim (Universitas Negeri Semarang, 2025)
The recalcitrant structure of lignocellulosic biomass necessitates efficient pretreatment strategies to enhance enzymatic saccharification for biofuel production. This study investigates a synergistic approach combining ultrasound irradiation with magnetic Fe₃O₄ for pretreating rice straw. A 2² factorial experimental design was employed to systematically evaluate the individual and combined effects of ultrasound (300 W, 30 min) and Fe₃O₄ addition (1.5 wt%). The combined treatment exhibited a pronounced synergistic effect, achieving 68.3% delignification and reducing the crystallinity index from 52.4% to 31.2%. These structural modifications resulted in a saccharification yield of 72.5%, which was significantly higher than the theoretical additive yield of 48.7% (raw: 18.5%, Fe₃O₄-only: 26.0%, ultrasound-only: 41.2%). SEM observations revealed extensive surface erosion, pore formation, and microfibril exposure after the combined pretreatment, while FTIR analysis confirmed substantial lignin removal. Furthermore, magnetic Fe₃O₄ demonstrated excellent magnetic separability, with a recovery efficiency higher than 95%, and maintained pretreatment performance over five reuse cycles with < 8% reduction in efficacy. Overall, this work presents a green, efficient, and economically promising pretreatment strategy based on synergistic ultrasound–magnetic Fe₃O₄ interactions, offering an effective pathway for enhancing lignocellulosic biomass saccharification and supporting the development of sustainable biorefinery processes.